HUBUNGAN MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR DENGAN HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP MTS AL-KHAIRIYAH KANGKUNG BANDAR LAMPUNG TAHUN PELAJARAN 2015/2016 - Aprilia, Rika (LPPM STKIP PGRI Bandar Lampung, 2016)
The problems of this study is the importance of students' motivation and learning environment either at home or at school that influence the learning outcomes of the Integrated Social Science subjects. The purpose of this study was to determine the relationship of learning motivation and learning outcomes of Integrated Social Science, to determine the relationship of the learning environment to learning outcomes of Integrated Social Science, and to determine the relationship of learning motivation and learning environment with learning outcomes at VIII class of MTs Al-Khairiyah Kale Bandar Lampung 2015/2016. The population in this study is VIII grade student consisted of 40 students. Questionnaire form is a questionnaire directly because researchers directly question to respondents. The survey results revealed that there is a positive and significant correlation between learning motivation and learning environment together on learning outcomes The result is evidenced by results of multiple correlation in calculation using SPSS version 20 for windows by using multiple regression analysis of the correlation coefficient (R) = 0.824, coefficient of determination (R Â²) equal = 0.678 and F value of = 39.016, when it is compared with the value of f table at a significance level of 5% that is equal to 3.25, the value> (39.016> 3.25).